Heritage and society: strategic guidelines for the digitization of the Lithuanian cultural heritage for the 2014–2020 programming period - Laužikas, Rimvydas; Varnienė-Janssen, Regina (Information & Media, 2015)
The article focuses on the strategic management of digitization in Lithuania. It elaborates on the development process of a conceptual approach to the creation of seamless content of the digital cultural heritage and presents the changing social context and a new paradigm of the legislation on the cultural heritage as well as its financing issues.The period of 2005–2009 should be considered a turning point in the cultural policy of Lithuania as the approval of the Concept for the Digitization of the Lithuanian Cultural Heritage and the Strategy for the Digitization of the Lithuanian Cultural Heritage, Digital Content Preservation and Access and its Implementation Framework in 2009–2013 by the Lithuanian government, which resulted in a new paradigm for the consolidation of memory institutions, oriented to cross-sectoral collaboration in digitizing Lithuania’s cultural heritage. These documents also provided more possibilities to receive financial support from the State budget and the EU Structural Funds for the digitization of the national cultural heritage and its long-term preservation and access. The major unsolved problems of the previous period have evolved from the inappropriate interpretation of strategic documents within the institutional environment. When interpreting these documents, conservative non-compatible institutional models were applied for strategic managing. Therefore, digitization was carried out without fully evaluating the social context and consolidating resources, thus resulting in poor quality digitization products, which were unrelated and satisfied the needs of institutions rather than of the users.The environment of the strategic management in the new programming period of 2014–2020 is shaped by the development of the network society, as it is defined by social sciences, the experience of the previous strategic period, and the highest level strategic documents defining the new period. The article also introduces the experience of the Martynas Mažvydas National Library of Lithuania and Vilnius University’s Faculty of Communication, activities by these and other twenty main cultural institutions of Lithuania in the development of the cultural and information society policy and the strategic management of cultural heritage digitization, and initiatives within these activities for the 2014–2020 programming period.